Neuroscience as a Component in Educational Setting. An Interpretive Overview - Farmakopoulou, Ignatia; Theodoratou, Maria; Gkintoni, Evgenia (Technium Education and Humanities, 2023)
In recent years, considerable advancements have been made in the field of educational neuroscience research. Researchers commend its existence and influence on educational procedures. This effort was intended to illustrate the educational applications of Neuroscience. In particular, research articles, quantitative and qualitative analyses, meta-analyses, and articles of critical inquiry on Neuroscience in Education were examined. In addition, a review of recent literature was attempted. From these studies, conclusions can be derived that can prove useful in the fields of research and teaching. Thus, best practices, methodologies, perspectives, attitudes, and perceptions that support the significance and value of Neuroscience in the field of education are offered.